Integrated transcriptomic and metabolomic analysis of flavonoid biosynthesis in cigar tobacco leaves under variable nitrogen regimes - Jia, Kai; Shi, Juanjuan; Bai, Lingli; Wang, Xueren; Wang, Yuemin; Li, Xiangzhen; Li, Wenqing; Zheng, Chaoyuan (Frontiers in Plant Science, 2025)
IntroductionFlavonoids are the most abundant secondary metabolites in plants and play important roles in plant growth, environmental adaptation, and human health. Tobacco serves as a vital cash crop and key source of flavonoids. Given tobacco's high nitrogen demand and the particular sensitivity of flavonoid synthesis to nitrogen supply, understanding the regulatory mechanisms of flavonoid biosynthesis under varying nitrogen conditions is essential.Methods and resultsWe systematically investigated the flavonoid biosynthesis pathways in the cigar tobacco cultivar Haiyan 204 under different nitrogen application rates using integrated transcriptomic and metabolomic analyses. This study identified 694 differentially expressed metabolites (DEMs) and 6,114 differentially expressed genes (DEGs). Integrated analyses revealed significant enrichment in the flavonoid biosynthesis and phenylpropanoid biosynthesis pathways. A regulatory network of flavonoid biosynthesis in response to nitrogen was constructed. Weighted gene co-expression network analysis (WGCNA) identified CHS2 as a key gene strongly associated with flavonoid biosynthesis, alongside its potential regulatory transcription factors MYB7, MYB9, bHLH14, and MYB_related1. The reliability of transcriptome data was validated via qPCR.DiscussionThese results provide a scientific basis for elucidating the biosynthesis mechanisms of tobacco flavonoids and identifying key nitrogen-responsive genes. The constructed regulatory network and identified transcriptional regulators offer critical insights into nitrogen-modulated flavonoid synthesis in cigar tobacco.